Class I PI3K Provide Lipid Substrate in T Cell Autophagy Through Linked Activity of Inositol Phosphatases - McLeod, Ian X.; Saxena, Ruchi; Carico, Zachary; He, You-Wen (Frontiers in Cell and Developmental Biology, 2021)
Autophagy, a highly conserved intracellular process, has been identified as a novel mechanism regulating T lymphocyte homeostasis. Herein, we demonstrate that both starvation- and T cell receptor-mediated autophagy induction requires class I phosphatidylinositol-3 kinases to produce PI(3)P. In contrast, common gamma chain cytokines are suppressors of autophagy despite their ability to activate the PI3K pathway. T cells lacking the PI3KI regulatory subunits, p85 and p55, were almost completely unable to activate TCR-mediated autophagy and had concurrent defects in PI(3)P production. Additionally, T lymphocytes upregulate polyinositol phosphatases in response to autophagic stimuli, and the activity of the inositol phosphatases Inpp4 and SHIP are required for TCR-mediated autophagy induction. Addition of exogenous PI(3,4)P2 can supplement cellular PI(3)P and accelerate the outcome of activation-induced autophagy. TCR-mediated autophagy also requires internalization of the TCR complex, suggesting that this kinase/phosphatase activity is localized in internalized vesicles. Finally, HIV-induced bystander CD4+ T cell autophagy is dependent upon PI3KI. Overall, our data elucidate an important pathway linking TCR activation to autophagy, via induction of PI3KI activity and inositol phosphatase upregulation to produce PI(3)P.